Análisis jurídico de la tenencia compartida de los hijos en casos de separación o divorcio de los progenitores en el cantón San Miguel en el año 2021. - Valverde Patín, María Michelle (2023)
The research will focus on the legal and doctrinal analysis of the shared custody of children during cases of separation or divorce of parents in the canton of San Miguel, province of Bolívar, in 2021. It is important to highlight that Ecuador is a constitutional state of rights and justice, as defined by the Ecuadorian Supreme Charter; Within this supreme norm there are contained rights, principles and guarantees that have been granted to the human being, within the constitutional principles is the best interest of children and adolescents which will be thoroughly analyzed in the development of the present investigation , since it is the obligation of the State to ensure the correct comprehensive development of all children and adolescents, especially when it comes to such a delicate issue as the custody of minors at the time of separation or divorce of the parents. . Shared custody is a novel issue that is characterized by attributing the custody of children and adolescents in equitable stable periods to both parents, giving rise to a correct comprehensive development of minors. For the development of this research, different methods will be used, such as inductive and deductive; At the same time, several research techniques and instruments will be used, which will allow me to get to know in depth the issue of shared custody after the separation or divorce of the parents in the canton of San Miguel, province of Bolívar. In relation to the expected results, I must indicate that, through this investigation, it is intended to determine if it is favorable to regulate the shared custody of parents in cases of separation or divorce. Keywords: Shared custody, best interests of the child, divorce.